2011
DOI: 10.1016/j.dza.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of guideline-endorsed treatments for low back pain: a systematic review

Abstract: Healthcare costs for low back pain (LBP) are increasing rapidly. Hence, it is important to provide treatments that are effective and cost-effective. The purpose of this systematic review was to investigate the cost-effectiveness of guideline-endorsed treatments for LBP. We searched nine clinical and economic electronic databases and the reference list of relevant systematic reviews and included studies for eligible studies. Economic evaluations conducted alongside randomised controlled trials investigating tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(77 reference statements)
1
2
0
Order By: Relevance
“…Our findings were compared to those of previous review of cost-effectiveness physiotherapy interventions or treatments for low back pain [14]. Parallel to the findings of the current review, previous literature found evidence to support that interdisciplinary rehabilitation, exercise, acupuncture, spinal manipulation, and cognitive behavioural therapy were cost-effective in patients with LBP.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our findings were compared to those of previous review of cost-effectiveness physiotherapy interventions or treatments for low back pain [14]. Parallel to the findings of the current review, previous literature found evidence to support that interdisciplinary rehabilitation, exercise, acupuncture, spinal manipulation, and cognitive behavioural therapy were cost-effective in patients with LBP.…”
Section: Discussionsupporting
confidence: 72%
“…Economic evaluation as a tool, for example, aims to improve the efficiency of healthcare resources in relation to physiotherapy interventions [13]. In previous reviews [6], a guideline endorsing treatments of interdisciplinary rehabilitation, exercise, acupuncture, spinal manipulation, and cognitive behavioural therapy was shown to be cost-effective for patients with chronic LBP [14]. However, there is inconsistency and lack of evidence on the costeffectiveness of some physiotherapy interventions including advisory consultation, medications, massage and yoga or relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal rehabilitation has shown evidence of reducing symptoms and disability [8,9]. The effects on sickness absence and work return are less consistent, but several studies have demonstrated reduced sickness absence after multimodal rehabilitation [10], while analyses of cost-effectiveness, including longitudinal follow-up studies [11] and analyses of cost-effectiveness have been positive [12]. Persons with less complex chronic pain conditions may benefit from unimodal treatments, i.e., physiotherapy, exercise or cognitive-behavioral therapy [13,14].…”
Section: Introductionmentioning
confidence: 99%